Collaborating With Student Parents as Participatory Researchers in a Qualitative Study. Issue 1 (January 2023) - Rauh, Lauren; Manze, Meredith G.; Watnick, Dana
When embarking on research within a community where little empirical research exists, the inclusion of a structured participant group—such as a steering committee or advisory board—can formalize the participant–research team partnership, increase community buy-in for action items, and reinforce the trustworthiness of research findings. These were among the aims of the multimethod design of the Student Parent Project, a qualitative study to determine the barriers and facilitators of academic achievement and well-being at six community colleges within a large, urban, public university system. The initial step of the study was to create a Student Advisory Board by recruiting one student parent from each of the participating campuses. The Student Advisory Board then met intermittently to review the research approach, data collection instruments, and preliminary findings at different stages. In this article, we describe the process of convening and collaborating with the advisory board and identify key areas in which their participation influenced the study design, findings, and recommendations. Based on lessons learned, we offer recommendations for the design and implementation of a participatory advisory board within qualitative studies.